Favipiravir treatment prolongs the survival in a lethal mouse model intracerebrally inoculated with Jamestown Canyon virus. - Hirofumi Kato; Mutsuyo Takayama-Ito; Masaaki Satoh; Madoka Kawahara; Satoshi Kitaura; Tomoki Yoshikawa; Shuetsu Fukushi; Nozomi Nakajima; Takashi Komeno; Yousuke Furuta; Masayuki Saijo (Public Library of Science (PLoS), 2021)
Background Jamestown Canyon virus (JCV) is a mosquito-borne orthobunyavirus that causes acute febrile illness, meningitis, and meningoencephalitis, primarily in North American adults. Currently, there are no available vaccines or specific treatments against JCV infections. Methodology/principal findings The antiviral efficacy of favipiravir (FPV) against JCV infection was evaluated in vitro and in vivo in comparison with that of ribavirin (RBV) and 2'-fluoro-2'-deoxycytidine (2'-FdC). The in vitro inhibitory effect of these drugs on JCV replication was evaluated in Vero and Neuro-2a (N2A) cells. The efficacy of FPV in the treatment of JCV infection in vivo was evaluated in C57BL/6J mice inoculated intracerebrally with JCV, as per the survival, viral titers in the brain, and viral RNA load in the blood. The 90% inhibitory concentrations (IC90) of FPV, RBV, and 2'-FdC were 41.0, 61.8, and 13.6 μM in Vero cells and 20.7, 25.8, and 8.8 μM in N2A cells, respectively. All mice infected with 1.0×104 TCID50 died or were sacrificed within 10 days post-infection (dpi) without treatment. However, mice treated with FPV for 5 days [initiated either 2 days prior to infection (-2 dpi-2 dpi) or on the day of infection (0 dpi-4 dpi)] survived significantly longer than control mice, administered with PBS (p = 0.025 and 0.011, respectively). Moreover, at 1 and 3 dpi, the virus titers in the brain were significantly lower in FPV-treated mice (0 dpi-4 dpi) versus PBS-treated mice (p = 0.002 for both 1 and 3 dpi). Conclusions/significance Although the intracerebral inoculation route is thought to be a challenging way to evaluate drug efficacy, FPV inhibits the in vitro replication of JCV and prolongs the survival of mice intracerebrally inoculated with JCV. These results will enable the development of a specific antiviral treatment against JCV infections and establishment of an effective animal model.